Facial Hyperpigmentation: A Rare Side Effect of Adalimumab - Malek Mrad MD; Mariam Tabka MD; Asmahane Souissi MD; Ines Chelly MD; Mourad Mokni MD (SAGE Publishing, 2024)
This report describes a case of facial hyperpigmentation in a patient with Crohn's disease receiving adalimumab, a tumor necrosis factor (TNF)-alpha inhibitor. The onset of hyperpigmentation coincided with adalimumab administration, and its discontinuation resulted in significant improvement. Histopathological findings suggest a postinflammatory process at the dermo-epidermal junction. However, the precise mechanism remains unclear.